The Concept of Government Treasurer: Indonesia Case Study - Sumantri, Joko; Fuady, Muhammad Syahrul (Yayasan Ilomata, 2024)
The determination of the functional position of treasurer which combines the duties of the treasurer with the Commitment-Making Officer (PPK) and Payment Instruction Signing Officer (PPSPM) has blurred the function of